Genomics and drug profiling of fatal TCF3-HLF-positive acute lymphoblastic leukemia identifies recurrent mutation patterns and therapeutic options - Fischer, Ute; Forster, Michael; Rinaldi, Anna; Risch, Thomas; Sungalee, Stéphanie; Warnatz, Hans-Jörg; Bornhauser, Beat; Gombert, Michael; Kratsch, Christina; Stütz, Adrian M; Sultan, Marc; Tchinda, Joelle; et al. (Nature genetics, 2015)
TCF3-HLF-positive acute lymphoblastic leukemia (ALL) is currently incurable. Using an integrated approach, we uncovered distinct mutation, gene expression and drug response profiles in TCF3-HLF-positive and treatment-responsive TCF3-PBX1-positive ALL. We identified recurrent intragenic deletions of PAX5 or VPREB1 in constellation with the fusion of TCF3 and HLF. Moreover somatic mutations in the non-translocated allele of TCF3 and a reduction of PAX5 gene dosage in TCF3-HLF ALL suggest cooperation within a restricted genetic context. The enrichment for stem cell and myeloid features in the TCF3-HLF signature may reflect reprogramming by TCF3-HLF of a lymphoid-committed cell of origin toward a hybrid, drug-resistant hematopoietic state. Drug response profiling of matched patient-derived xenografts revealed a distinct profile for TCF3-HLF ALL with resistance to conventional chemotherapeutics but sensitivity to glucocorticoids, anthracyclines and agents in clinical development. Striking on-target sensitivity was achieved with the BCL2-specific inhibitor venetoclax (ABT-199). This integrated approach thus provides alternative treatment options for this deadly disease.
Keywords: Sequence Deletion; exprese genu; Gene Expression; DNA Mutational Analysis; sekvenční delece; genetické asociační studie; Male; kohortové studie; mutace; protinádorové látky; Cohort Studies; Mice, SCID; Genetic Association Studies; Immunoglobulin Light Chains, Surrogate; Kaplan-Meier Estimate; Xenograft Model Antitumor Assays; chemorezistence; Kaplanův-Meierův odhad; mužské pohlaví; fúzní onkogenní proteiny; Genomics; Inhibitory Concentration 50; akutní lymfatická leukemie; mutační analýza DNA; Coculture Techniques; myši inbrední NOD; xenogenní modely - testy protinádorové aktivity; Oncogene Proteins, Fusion; Animals; lidé; ženské pohlaví; Humans; zvířata; myši SCID; náhradní lehké řetězce imunoglobulinů; PAX5 Transcription Factor; kokultivační techniky; inhibiční koncentrace 50; Drug Resistance, Neoplasm; Mutation; aktivátorový protein specifický pro B-buňky; Female; Mice, Inbred NOD; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Antineoplastic Agents; genomika